2010
DOI: 10.1179/030192309x12506804200465
|View full text |Cite
|
Sign up to set email alerts
|

Causes of transverse corner cracks in microalloyed steel in vertical bending continuous slab casters

Abstract: Transverse corner cracks have been frequently observed and are extremely difficult to prevent in some microalloyed steels produced on some vertical bending type continuous slab casters. The cracks are usually found on the fixed (outer) side corner of the slabs through inspection of the acid pickled surface and macroscopic examination. In the present study, the slab surface microstructure was investigated, and the results show that the causes of the crack formation are chain-like precipitations and film-like pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…In the SSC temperature scheme, there is a reheating period mainly due to heat conduction (physical and latent heat) from the core to surface or corner of the slab. Combining previous research [13][14][15][16][17][18], the reheating rate of 3 • C/s is assumed in this paper. 4# sample was heated to 1350 • C, held for 5 min, cooled to 600 • C with a cooling rate of 10 • C/s, held for 2 min, reheated to 1100 • C with a reheating rate of 3 • C/s, and then quenched.…”
Section: Ssc Process Test Schemementioning
confidence: 99%
See 1 more Smart Citation
“…In the SSC temperature scheme, there is a reheating period mainly due to heat conduction (physical and latent heat) from the core to surface or corner of the slab. Combining previous research [13][14][15][16][17][18], the reheating rate of 3 • C/s is assumed in this paper. 4# sample was heated to 1350 • C, held for 5 min, cooled to 600 • C with a cooling rate of 10 • C/s, held for 2 min, reheated to 1100 • C with a reheating rate of 3 • C/s, and then quenched.…”
Section: Ssc Process Test Schemementioning
confidence: 99%
“…Suzuki et al [16] believed that the reconstructed austenite grains only shifted, while the grain size did not change. Owing to a low temperature stage in the thermal schedule of the SSC process, Walmag et al [13], Lee et al [17], and Ma et al [18] believed that the growth time of original austenite grains was reduced, and the new austenite grains were nucleated around the ferrite grain boundary during the process of re-austenite transformation, and the newly formed austenite grains became smaller. Du et al [19] also pointed that the austenite grain grows a little bit rather than being refined after a γ-α-γ transformation.…”
Section: Introductionmentioning
confidence: 99%
“…In the formula, t c is the cooling rate, KAEs À1 ; R p is the radius of precipitation particle, nm; and A, B, C, and n are the coefficients, related to the composition of steel, cooling rate, and other thermodynamic conditions during the process of cooling. Equations [3] and [4] are expressed as follows:…”
Section: Density and Volume Fraction Of The Second-phase Precipitamentioning
confidence: 99%
“…The precipitation of carbonitrides accelerates the nucleation of proeutectoid ferrite and forms a wide, net-like film of proeutectoid ferrite along the grain boundary. [3,4] The slab hot ductility would be significantly reduced by the formation of this kind of microstructure, and hence, the crack would be more likely to be introduced. [5,6] It also was studied that the hot ductility of microalloyed steel was influenced by the precipitation of carbonitride's volume fraction, size, shape, and distribution, and the larger volume fraction, bigger size as well as the netor chain-like shape with nonuniform distribution are more harmful to the hot ductility.…”
mentioning
confidence: 99%
“…Papaefthymiou et al through the use of SEM with EDS analysis, found that the transverse cracking is attributed to copper or casting powder entrapment, thus determining that the crack occurred in the mold. Ma et al could not find any slag inclusion in cracks, but found both the chain‐like carbonitrides and film‐like proeutectoid ferrite distribution along the grain boundaries, indicating that the generation position of the transverse corner cracks was in the bending segment of the continuous caster. Takeuchi et al found that transverse cracks exhibited an interdendritic appearance located in the trough of oscillation marks, which implied that the cracks were initiated in the mold of the continuous caster.…”
Section: Introductionmentioning
confidence: 96%